The Relationship of Large-Artery Atherothrombotic Stroke with Plasma Trimethylamine N-Oxide Level and Blood Lipid-Related Indices: A Cross-Sectional Comparative Study. (23rd April 2021) - Xu, Dongjuan; Zhao, Wenfeng; Song, Juexian; Yin, Lu; Wang, Kun; Wei, Lianyan; Xu, Yunyun; Li, Hongfei; Min, Baoquan; Tang, Ning; Jiang, Xiaoyan; Liu, Hui; et al.
Abstract : Objective . The role of trimethylamine N-oxide (TMAO) in cardiovascular diseases has been highlighted. Nevertheless, the associations of large-artery atherosclerotic (LAA) stroke with TMAO and blood lipid-related indices are little investigated. Methods . A cross-sectional comparative study was performed on 50 patients with LAA stroke and 50 healthy controls. Basic demographic data, common vascular risk factors, and blood lipid-related indices were collected. Plasma TMAO was detected through liquid chromatography tandem mass spectrometry. Multivariable unconditional logistic regression analyses were run to assess the associations of LAA stroke with plasma TMAO level and blood lipid-related indices. The area under the curve (AUC) of the receiver operating characteristic (ROC) was computed to assess the diagnostic performance of plasma TMAO level and blood lipid-related indices for LAA stroke. Results . Compared with healthy controls, the elevated plasma TMAO level (odds ratio [OR], 7.03; 95% confidence interval [CI], 2.86, 17.25; p < 0.01 ) and Apo-B (OR, 1.74; 95% CI, 1.06, 2.85; p = 0.03 ) were observed in LAA stroke patients, while lower Apo-A1 (OR, 0.56; 95% CI, 0.34, 0.91; p = 0.02 ), Apo-A1 to Apo-B ratio (OR, 0.29; 95% CI, 0.15, 0.56; p < 0.01 ), and HDL-C (OR, 0.56; 95% CI, 0.35, 0.91; p = 0.02 ) were found in LAA stroke patients after adjusted for age and gender. Moreover, plasma TMAO (AUC, 0.89; 95% CI, 0.83, 0.95), Apo-A1 (AUC, 0.81; 95% CI, 0.72, 0.89), Apo-B (AUC, 0.81; 95% CI, 0.73, 0.90), Apo-A1 to Apo-B ratio (AUC, 0.85; 95% CI, 0.78, 0.93), and HDL-C (AUC, 0.81; 95% CI, 0.72, 0.89) showed good diagnostic values for LAA stroke in adjusted models. Conclusions . The plasma TMAO level, Apo-A1, Apo-B, and HDL-C are important biomarkers for LAA stroke patients.